2016
DOI: 10.1109/lcomm.2016.2564971
|View full text |Cite
|
Sign up to set email alerts
|

Prime Block Design for Asynchronous Wake-Up Schedules in Wireless Sensor Networks

Abstract: Due do the various requirements of sensor applications, it is desired to design a neighbor discovery protocol that supports both symmetric and asymmetric duty cycles. This letter proposes a new block-based neighbor discovery protocol for asymmetric sensor networks by adapting the theory of balanced incomplete block designs and the Chinese remainder theorem. Through the simulation study, it is demonstrated that the proposed block-based neighbor discovery protocol outperforms other neighbor discovery methods, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Many asynchronous neighbor discovery algorithms have emerged in recent years. Based on whether the discovery latency is finite or not, existing pairwise asynchronous protocols are divided into the probabilistic algorithms [12,19,20] and deterministic ones [8,[21][22][23][24][25][26][27][28].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Many asynchronous neighbor discovery algorithms have emerged in recent years. Based on whether the discovery latency is finite or not, existing pairwise asynchronous protocols are divided into the probabilistic algorithms [12,19,20] and deterministic ones [8,[21][22][23][24][25][26][27][28].…”
Section: Related Workmentioning
confidence: 99%
“…Searchlight-Striped [7], Non-integer [25] and Lightning [26] are included. There are other related methods, i.e., block-based methods [8,27] and Nihao [28]. In block-based methods, block theory is used to obtain a wakeup schedule.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], Lee et al, introduced a new approach called an OR-based neighbor discovery protocol that can support both symmetric and asymmetric neighbor discovery in sensor networks. In [15], they further extended the block design based method using a prime number in order to support a network with asymmetric duty cycles. However, the method extends the length of the discovery cycle significantly, and the discovery latency may increase considerably in the worst case.…”
Section: Related Workmentioning
confidence: 99%
“…In [14,15], it was shown that ( )-BIBD cannot support asymmetric duty cycle. In order to solve this problem, we propose the new NDP method that combines several ( )-BIBD blocks using a bitwise exclusive OR (XOR) operation.…”
Section: Figure 3 An Example Of Two Asymmetric Bibd-based Schedules mentioning
confidence: 99%